Horizontal accountability and the challenges for democratic consolidation in Africa: evidence from Liberia. Issue 7 (9th November 2016) - Signé, Landry; Korha, Koiffi
ABSTRACT: Why are most African emerging democracies failing to consolidate and reach the two-turnover test? Most scholars attribute this to the poor quality of elections and limited institutionalization of vertical accountability, overlooking some important variables. This article challenges this conception both theoretically and empirically by focusing on the quality of horizontal accountability illustrated by observations of comparative interest in Liberia's emerging democracy. Since the end of Liberia's bloody civil war in 2003, two successive and successful democratic elections (2005 and 2011) have been organized, putting Liberia on the path towards democratic consolidation. When analysing the electoral mechanism of vertical2016 accountability, many scholars have been enthusiastic about the prospects of democratic consolidation in Liberia, most of them neglecting the horizontal accountability processes that are also crucial for the quality and durability of democracy. This article analyses the processes and challenges of democratic consolidation in Liberia by focusing on key institutions of horizontal accountability. It argues that although the country has made some progress towards democratization since 2005, the domination and centralization of executive power, weak and dependent institutions of horizontal accountability (legislature, judiciary, national elections commission, general auditing commission, and anti-corruption commission) are major challenges to the consolidation of democracy. These findings have important implications for our understanding of horizontal accountability and democratic consolidation in African emerging democracies.